APLIKASI DATA PASIEN RAWAT INAP PADA PUSKESMAS PAGELARAN MENGGUNAKAN DATABASE MYSQL DAN BAHASA PEMROGRAMAN PHP - Restiana, Nila (JMBI (Journal of Marketing and Business Intelligence), 2024)
The making of in-patient data application data at a Puskesmasis very important, so that patients and residents living in the distant and near of Puskesmas can quickly obtain information and make it easier about registration through an application in order not to take a lot of time. Unfortunately in this digital era there are still some Puskesmas that still use manual system in searching patient data and registration which still using ancient equipment that is not accurate in creating a decision. To improve the performance and ease in the management of services at PuskesmasPagelaran then proposed an application that can facilitate and improve in service. Information system application at PuskesmasPagelaran is equipped with user login menu and in the application there are user pages and patient data search. The purpose of this study is to help the existing service system in the Puskesmas to further facilitate the process of registration of patients and to help users, especially at the PuskesmasPagelaran in the management of inpatients data electronically by building an information system that utilizes the PHP programming language and MySQL database